Optimisation of the design of a steel-welded pressure hull structure based on interactive nonlinear collapse strength analyses. (2nd January 2022) - Muttaqie, Teguh; Park, Sang Hyun; Cho, Sang-Rai; Sohn, Jung Min
ABSTRACT: In this study, the genetic algorithm (GA) was implemented for the multi-objective optimization of the structural design of a pressure hull. The objective functions sought the maximum ultimate strength of the ring-stiffened cylindrical shell structure with minimum structural weight and maximum volume of the configured structural member. First, the evaluation models of several design variables of submarine structures were studied. Subsequently, a multi-objective GA algorithm was introduced. To improve the quality of the new population, several design constraints are applied. The final candidate structures were recomputed by non-linear finite element analysis (FEA) to observe the failure modes and compared with the initial design model. The results suggest that a lightweight construction would be achieved when a material with higher strength is used, especially for greater design depths